1992
DOI: 10.2307/1591501
|View full text |Cite
|
Sign up to set email alerts
|

Restriction Endonuclease Analysis of Pasteurella multocida Isolates from Three California Turkey Premises

Abstract: Three California turkey premises that had repeated outbreaks of fowl cholera were studied for periods of 2 to 4 years. Using biochemical, serologic, plasmid DNA, and restriction endonuclease analyses of isolates of Pasteurella multocida from turkeys and wildlife on the premises, strains of the organism were found to be enzootic on two of the premises. On the third, a variety of strains of P. multocida were isolated from fowl cholera outbreak flocks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…There have been many studies on the epidemiology of fowl cholera outbreaks in a variety of hosts; for example, in turkeys (Snipes et al, 1989(Snipes et al, , 1990Christiansen et al, 1992;Blackall et al, 1995;Kardos & Kiss, 2005), geese (Kardos & Kiss, 2005), free-range layers (Zhang et al, 2004), conventional layer flocks (Shivachandra et al, 2005;Eigaard et al, 2006), backyard poultry (Christensen et al, 1998) and ducks (Muhairwa et al, 2000). Unlike these prior studies, our current study has used both a phenotypic method (Heddleston serotyping) as well as a genotypic method (MLST).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been many studies on the epidemiology of fowl cholera outbreaks in a variety of hosts; for example, in turkeys (Snipes et al, 1989(Snipes et al, , 1990Christiansen et al, 1992;Blackall et al, 1995;Kardos & Kiss, 2005), geese (Kardos & Kiss, 2005), free-range layers (Zhang et al, 2004), conventional layer flocks (Shivachandra et al, 2005;Eigaard et al, 2006), backyard poultry (Christensen et al, 1998) and ducks (Muhairwa et al, 2000). Unlike these prior studies, our current study has used both a phenotypic method (Heddleston serotyping) as well as a genotypic method (MLST).…”
Section: Discussionmentioning
confidence: 99%
“…In some studies, there have been multiple genotypes associated with outbreaks in turkeys (Snipes et al, 1989(Snipes et al, , 1990Christiansen et al, 1992). In contrast, other outbreaks have been reported as being associated with a single clone; for example, in turkey flocks (Blackall et al, 1995), in free-range layers (Zhang et al, 2004), in conventional layer flocks (Shivachandra et al, 2005;Eigaard et al, 2006) and in backyard poultry (Christensen et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…1,5 The finding of a single clone within a property is not universal as 1 previous study has shown the presence of multiple REA types within 1 of the 3 turkey farms studied. 5 The only previous molecular study of fowl cholera outbreaks with time involved a Muscovy duck farm. 13 This farm was a multiage farm with a yearly cleanup period in which no bird was present on the property.…”
mentioning
confidence: 90%
“…15 Molecular techniques such as restriction endonuclease analysis (REA) and ribotyping have enabled researchers to distinguish clones of P multocida as a method of studying outbreaks of fowl cholera in turkeys. 1,2,4,5,11 However, there are only lim-ited reports of the use of these techniques for fowl cholera outbreaks associated with chickens. 3,13,14 In this report, the use of REA and conventional biochemical and serological typing to examine the molecular epidemiology of 2 acute outbreaks of fowl cholera, separated by 8 years, on a free-range layer farm is described.…”
mentioning
confidence: 99%
“…multocida has been found worldwide in association with various disease conditions in a broad range of hosts, including mammals and both domesticated and wild birds (Frank, 1989;Glisson et al ., 2003). Previous epidemiological investigations have demonstrated that P. multocida associated with fowl cholera in single domestic turkey flocks may belong to multiple clones (Snipes et al ., 1989(Snipes et al ., , 1990Christiansen et al ., 1992;Rhoades et al ., 1992), indicating the importance of characterizing multiple isolates from fowl cholera outbreaks to obtain reliable epidemiological information. The association of a single clone with outbreaks of fowl cholera has been reported in turkey (Christiansen et al ., 1992;Blackall et al ., 1995) and layer flocks (Zhang et al ., 2004), but this was based on relatively few isolates.…”
Section: Introductionmentioning
confidence: 99%